Children who commit acts of serious interpersonal violence : messages for best practice - Hagell, Ann; Jeyarajah-Dent, Renuka (Jessica Kingsley Publishers, 2006)
Children Who Commit Acts of Serious Interpersonal Violence explores risk management and successful intervention for children in public care who have committed, or are at risk of committing, acts of serious violence. The contributors identify different subgroups of children who are difficult to place, including those who sexually offend and those who murder, and outline the key characteristics and patterns of need they display. They provide an overview of the risk factors leading to extremely violent behaviour and discuss the complexities of diagnosis and definition from a multidisciplinary per.